Local Community Legal Understanding of Communal Intellectual Property as an Instrument for Environmental Protection in the Borobudur National Strategic Tourism Area - Rani Pajrin; Itok Dwi Kurniawan; Muhammad Fachrie (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Communal Intellectual Property (CIP) represents collective rights over traditional knowledge, cultural expressions, genetic resources, and geographical indications that are integral to the identity and ecological wisdom of local communities. In Indonesia, recent regulatory developments, particularly Government Regulation No. 56 of 2022, seek to strengthen the protection of CIP; however, the effectiveness of these legal instruments largely depends on the legal understanding and participation of custodial communities. This study examines local community legal understanding of communal intellectual property as an instrument for environmental protection in the Borobudur National Strategic Tourism Area (Kawasan Strategis Pariwisata Nasional Candi Borobudur), a priority tourism destination characterized by intense interaction between cultural heritage, environmental sustainability, and tourism development. Adopting a socio-legal approach, this research combines normative legal analysis with empirical fieldwork. Primary data were collected through structured questionnaires administered to sixty-seven respondents across multiple villages within the Borobudur area, complemented by qualitative interpretation of open-ended responses. The findings reveal a paradoxical pattern: while a strong majority of respondents express normative support for the protection and preservation of communal intellectual property, levels of awareness regarding formal legal frameworks and regulatory instruments remain low. Knowledge and legal literacy are unevenly distributed, with higher awareness concentrated among village government officials, while elders and non-institutional custodians of traditional knowledge are underrepresented. The study also identifies rich domains of communal intellectual property, including traditional agricultural knowledge, cultural performances, handicrafts, and plant-based genetic resources, all of which possess direct relevance to environmental stewardship. However, limited legal understanding constrains the ability of communities to operationalize communal intellectual property through mechanisms such as documentation, registration, free, prior and informed consent (FPIC), and access and benefit sharing (ABS). These gaps undermine the potential of CIP to function as an effective instrument for environmental protection in the context of sustainable tourism. This research contributes to the literature by providing empirical evidence on community legal understanding of CIP and by highlighting the need for participatory, community-centered governance mechanisms. It argues that strengthening legal literacy, inclusive documentation, and co-governance arrangements is essential to align communal intellectual property protection with environmental sustainability objectives in the Borobudur National Strategic Tourism Area.